The Impact of Green Trade Openness on Air Quality - van Hinsberg, Nicky; Can, Muhlis (Ekonomikalia Journal of Economics, 2024)
Environmental degradation is among the most pressing issues the world faces today. Air pollution is one of the many forms of environmental degradation and can drastically impact human health and ecosystem functioning. Research shows that rapid intervention strategies are required to achieve the environmental targets set out by international agreements. One strategy that has been widely accepted to combat this issue of environmental degradation is the introduction of green products. The adoption of green products can be increased through trade. However, knowledge of the impact of trading these products is limited. This study examines the relationship between the trading of green products and air quality in a case study of 33 Organization for Economic Cooperation and Development (OECD) member countries from 2003-2016. We employ several panel strategies, such as the Westerlund (2008) Durbin-H method for cointegration and the Method of Moments Quantile Regression (MM-QR). The trading of green products was proxied by the newly developed ‘Green Openness Index.’ Nitrous oxide (NOx) and sulfur oxide (SOx) emissions served as proxies for air pollution. The relationship between the variables was explored in the context of the Environmental Kuznets Curve (EKC). The cointegration analysis reveals that there is a long-run relationship among the series. Long-run estimations prove that the EKC hypothesis is valid for the analyzed series. Additionally, the empirical findings reveal that trading environmentally friendly products increases air quality while energy consumption decreases. We provide several policy suggestions based on the study’s outcomes, such as supporting the trade liberalization of green goods, reducing tariff and non-tariff barriers for environmentally friendly products, and promoting the adoption of environmentally friendly goods by providing subsidies and other tax incentives to consumers.